SPECIALIZED SPEED TRAINING DRILLS CORRESPONDING TO VARIOUS PITCH POSITIONS AND THEIR IMPACT ON SELECTED SOCCER SKILLS AMONG YOUNG PLAYERS (American Journal of Pedagogical and Educational Research, 2023)
The objectives of this research are to prepare specialized exercises for developing the speed attribute according to different playing positions among the research sample individuals. It also aims to identify the impact of these specialized exercises on enhancing the speed attribute according to different playing positions among the research sample individuals. Additionally, the research seeks to examine the influence of the speed attribute on some fundamental soccer skills according to different playing positions among the research sample individuals. Chapter Three includes the research methodology (experimental approach) and the sample consisting of 20 players divided into two groups (control and experimental) based on the playing positions (4 for defense, 4 for midfield, and 2 for attack). The methodology also includes specialized exercises for developing speed attributes according to different playing positions. The researchers utilized tests related to speed attribute and soccer skills, with the program comprising 24 training units, conducted over three training sessions per week for eight weeks. The survey was conducted on a sample from the same original community and the main experiment, which is the youth club of Mosul. Additionally, the researchers used the SPSS statistical package to extract the statistical results. Specialized exercises have a positive impact on developing the speed attribute according to different playing positions for defense, midfield, and attack in the experimental group. They also have a positive effect on some skills (dribbling, shooting, and running with the ball). Furthermore, specialized exercises for transitional speed had the greatest impact on the development percentage for attacking players. One of the key recommendations is to utilize these specialized speed exercises for young players under the supervision of coaches, as they have a positive impact on the players' performance, considering that young players are the real prospects. Additionally, there should be an emphasis on diversifying specialized training methods for speed and focusing on the special preparation stage, highlighting the importance of skill and tactical preparation. These exercises can also be used for advanced teams and different age groups.